Crecimiento económico y su relación con la calidad de vida del Distrito de Sauce periodo 2010 a junio de 2015 - Saavedra Gómez, Paul Ernesto (2015)
This research entitled "economic growth and its relationship with the quality of life of the District of willow period 2010 to June 2015", aimed at determining the relationship between economic growth and the quality of life of the District of willow period 2010-2015. For which they had a sample comprised the total population under study of the District of willow, in 2010, 2011, 2012, 2013, 2014 and to June 2015 periods, which can then be analyzed and results reached the following conclusions: that the economic growth of the Willow district is growing so little significant but steady This is demonstrated by their studied indicators, also the quality of life of the District of willow has improved in the last 5 years, steadily. "Therefore with fashion the results obtained could be concluded that there is a direct relationship between economic growth and the quality of life of the District of willow, this was demonstrated by the implementation of the Student" t" test, where the t" calculate resulted 3.82, and tabular "t" is of 2.015, which demonstrated that the results obtained are within the region of rejection of the null hypothesis, and so it is ruled out it the hypothesis that there is no direct relationship between the variables studied.